Evaluasi Kualitas Nutrien Dedak Gandum Hasil Olahan Enzim yang Diproduksi Aspergillus niger dan Trichoderma viride pada Ransum Ayam Broiler - N Ramli; R A Haryadi; D G Dinata (Media Peternakan, 2005)
An addition of crude enzyme from A. niger and T. viride was done to increase nutrien quality of wheat bran with an addition of commercial enzyme as a comparison. Nutrient composition, metabolizable energy and performance of broiler were parameters observed to evaluate the improvement. Enzymes from A. niger, T. viride and commercial enzyme were capable of decreasing fiber and increasing metabolizable energy of wheat bran. Crude fiber content of wheat bran decreased by 14.86%, 8.24% and 0.36%, true metabolizable energy increased by 8.25%, 7.98% and 2.22% when wheat bran was treated with enzymes from A. niger, T. viride and commercial enzyme, respectively. Except for wheat bran treated with commercial enzyme, utilization of wheat bran-treated enzymes from A. niger and T. viride could increase feed intake, daily gain and final weight of broilers. However, the enzyme addition did not improve feed conversion. It is concluded that the addition of enzymes from A. niger and T. viride could improve nutrient quality of wheat bran. Key words : wheat bran, crude enzymes, T. viride, A. niger, broilers